Spoiling the party. Experimental evidence on the willingness to transmit inconvenient ethical information - Jantsje M. Mol; Ivan Soraperra; Joël J. van der Weele (Tinbergen Institute, 2023)
Information about the consequences of our consumption choices can be unwelcome, and people sometimes avoid it. We investigate a situation where one person possesses information that is inconvenient for another, and study why and when they decide to transmit that information. We introduce a simple and portable experimental game to analyze transmission of inconvenient information. In this game, a Sender can inform a Receiver at a small cost about a negative externality associated with a tempting and profitable action for the Receiver. The results from our online experiment (N = 1,512) show that Senders transmit more information for large negative externalities. Sender's decisions are largely driven by their own preferences for information. However, some Senders take the Receiver's feelings into account, by transmitting evidence of positive externalities or by suppressing negative information upon the Receiver's request. Understanding the decision to share inconvenient information matters, as it will affect the personal and political will to address important externalities and can inform strategies to encourage the transmission of inconvenient information within organizations.
Keywords: B41; C91; C93; 330; willful ignorance; information avoidance; unethical behavior; lab experiment